Evaluation of the Quality of the Elementary Education Program at Farhangian University Based on the CIPP Model - Esmaeilbeygi, Hamide; Abdollahi, Bijan; Navehebrahim, Abdolrahim; Abbasian, Hossein (Iranian Journal of Educational Sociology, 2022)
Purpose: One of the fields with the highest number of students at Farhangian University is Primary Education. Therefore, the purpose of this study was to evaluate the quality of the Primary Education program at Farhangian University based on the CIPP model. Methodology: This study was applied in terms of objective and descriptive-survey in terms of implementation method. The study population included faculty members, educational group managers, and graduates of Primary Education from Farhangian University campuses in Tehran province during 2019-2022, and primary school principals in Tehran city in 2022. The sample size was estimated to be 276 individuals (20 faculty members, 6 educational group managers, 200 graduates of Primary Education, and 50 primary school principals) selected through simple random sampling. Data were collected through semi-structured interviews with faculty members and educational group managers and a researcher-made questionnaire filled out by all sample members. The data were analyzed using open, axial, and selective coding methods and examining the desirability of axial and selective codes. Findings: The findings indicated that for the quality of the Primary Education program at Farhangian University based on the CIPP model, 88 open codes, 31 axial codes, and 7 selective codes were identified. Conclusion: The results of this study indicated that the status of the Primary Education program at Farhangian University based on the CIPP model was not at a desirable level and improvement of the identified open, axial, and selective codes in this research is necessary for enhancement.